Hanseníase em menores de quinze anos no Amazonas: aspectos clínicos e epidemiológicos e distribuição espacial - Ribeiro, Ully Karina da Silva (Brasil, 2024)
Introduction: Leprosy is an infectious, transmissible, and chronic disease that can cause severe and permanent physical disabilities. Children under 15 years old affected by this illness, without early diagnosis or proper treatment, may acquire sequelae that will affect their adult life. Objective: To identify the epidemiological, clinical aspects, and spatial distribution of reported leprosy cases in individuals under 15 years old in the state of Amazonas between 2002 and 2021. Method: This is an epidemiological, ecological, and retrospective research, using secondary data from the Notifiable Diseases Information System available in the database of the Unified Health System's Informatics Department. The detection rate of cases per year was calculated, and descriptive analyses were performed using Microsoft Excel, and the Quantum GIS (QGIS) software, version 2.18.6, for map analysis and construction. Results: A total of 1,471 cases were reported, with a prevalence of: female sex (51.3%), age between 10 and 14 years (70.2%), mixed race (67.9%), residence in rural areas (62.5%), paucibacillary operational classification (63.6%), tuberculoid clinical form (32.9%), grade 0 physical disability in the notification (80.6%) and in the cure (63.3%). Over the years, a decrease in the detection rate was observed. Conclusion: Considering the high endemicity of leprosy in children under 15 years old in the Amazonas region, the importance of developing more effective disease control and dissemination strategies, as well as prevention of disabilities, particularly in children, is emphasized.